Transport and Wellbeing of Public Housing Tenants—A Scoping Review - Edward Randal; Amber Logan; Guy Penny; Mary Anne Teariki; Ralph Chapman; Michael Keall; Philippa Howden-Chapman (Urban Science)
The role of public housing in improving wellbeing for tenants and society is an important public policy issue. Public housing tenants in Aotearoa New Zealand have constrained incomes and their mode of transport has implications for their budgets, their wellbeing, and carbon emissions. Tenants’ daily life choices and wellbeing are influenced by the set of transport options available to them and the constraints and opportunities these options entail. What is important for wellbeing is also dependent on culture. Little is known, however, about the specific influences of transport on the wellbeing of public housing tenants and how that is mediated by the culture of particular groups, particularly Māori and Pacific people, who make up the majority of people in public housing in Aotearoa. In this article we review the literature on public housing, transport, and wellbeing, to establish what is known about how transport, and the access it affords, influence the wellbeing of public housing tenants. We searched Scopus and Web of Science for academic journal articles, published in English and available online, about public housing tenant wellbeing with regard to the transportation and location characteristics of public housing. We found that creating highly accessible public housing developments with options of various modes of travel is important for the wellbeing of tenants. We also found that understanding the specific needs and preferences of tenants, ensuring tenants have agency over how they travel, and engaging with tenants during transport decision-making are particularly important and often under-recognised for people in public housing. Finally, we identified substantial gaps in the literature around understanding transport needs and experiences from Māori and Pacific perspectives, emphasising the importance of including indigenous and ethnic minority views in future research.